Application of the CAB evaluation of thermal scattering law for heavy water to ZED-2 critical benchmarks at room temperature. (December 2017) - Roubtsov, D.; Chow, J.C.; Márquez Damián, J.I.; Granada, J.R.
Abstract: To improve the evaluations in thermal scattering sub-libraries, a set of thermal neutron scattering cross sections (scattering kernels) was developed recently at Centro Atómico Bariloche (CAB) for deuterium and oxygen bound in liquid heavy water, and made available in the ENDF-6 format. These libraries are based on a combination of results of molecular dynamics (MD) simulations and recent experimental data and, when used, result in an improvement of calculations of observables of single neutron scattering experiments, compared to results based on previous evaluations. In this work, we provide additional details on the CAB evaluation of heavy water at room temperature and discuss the important integral characteristics of neutron scattering kernels, such as the cross sections, average scattering cosine, and average secondary energy. Then, the new set of thermal scattering kernels is applied in modelling criticality of the ZED-2 reactor, and the international benchmarks LEU-MET-THERM-003 (ICSBEP handbook) and ZED2-HWR-EXP-001 (IRPhEP handbook) are analyzed in detail. The differences in the estimates of criticality due to changes in the S ( α, β ) data from the reference one (ENDF/B-VII) to the CAB evaluation are 100–200 pcm; they are comparable but smaller than the ZED-2 benchmark uncertainties ( ≈ ± 300  pcm). Changing the reference evaluation of 16 O to the recently developed one from the CIELO project (WPEC subgroup 40) results in a decrease of criticality by ∼ 100  pcm. Using different combinations of the improved nuclear data for deuterium, oxygen, and the CAB TSL model, we obtain biases up to 300–400 pcm in the estimates of criticality of the selected ZED-2 benchmarks. Application of the new evaluations for 235 U and 238 U from the CIELO project improves the estimates of k eff by decreasing the bias by ∼ 100  pcm that indicates a need for further investigations of the ZED-2 critical assemblies.